835 CARDIOMYOPATHIES: IS IT USEFUL TO ANALYZE MINOR GENES?. (15th December 2022) - Mazzaccara, Cristina; Barretta, Ferdinando; Uomo, Fabiana; Caiazza, Martina; Monda, Emanuele; Lombardi, Raffaella; Losi, Maria Angela; Limongelli, Giuseppe; D´argenio, Valeria; Frisso, Giulia
Abstract: The diffusion of Next Generation Sequencing (NGS)-based approaches has allowed the identification of cardiomyopathies and channelopathies pathogenic mutations in more than 200 different genes. Since also genes considered uncommon for a clinical phenotype are now included in molecular testing, the detection rate of disease-causing variants is increased. Here, we report the prevalence of genetic variants detected in a cohort of 133 patients, among which 73 showed complex or borderline phenotypes or a positive family history for SCD. The analysis was conducted by analyzing an enlarged panel of 129 genes, including 60 main genes associated to the different genetic cardiomyopathies (HCM, DCM, ACM, LQTS, BrS) and 69 genes without a strong or definitive evidence of disease association according to the NIH-funded Clinical Genome Resource (ClinGen), here named "uncommon genes". We identified 82 variants, of which 50 (61%) were identified in uncommon genes. Among these, thirty-five (70%) were reported as variants of unknown significance (VUSs), thirteen (26%) as pathogenic (P) or likely pathogenic (LP) mutations and 2 (4%) as novel (likely) benign (B/LB) variants, according to the American College of Medical Genetics (ACMG) classification. Interestingly, about 85% of P/LP variants identified in uncommon genes were in patients showing complex/unclear/borderline phenotypes or a positive family history for SCD. These data support the need for an extended genetic testing, including genes that are not usually explored due to a currently poor association with the clinical phenotype, particularly when phenotype is borderline, in order to increase the diagnostic sensitivity of inherited cardiomyopathies and channelopathies genetic testing.